Near-field velocity pulse-like ground motions on February 6, 2018 MW6.4 Hualien, Taiwan earthquake and structural damage implications - Ji, Kun; Ren, Yefei; Wen, Ruizhi; Kuo, Chun-Hsiang (Soil dynamics and earthquake engineering (1984), 2019)
The February 6, 2018 Hualien Taiwan Earthquake (Mw6.4) had caused serious fatalities and severe building damages in Hualien city. Substantial near-field velocity pulse-like ground motions were probably one of the important factors. We used the continuous wavelet transforms method to identify the velocity pulse-like ground motions from orthogonal components of all the recorded ground motions. The identification results were in agreement with the contour map of pulse-like occurrence probability according to two prediction models for non-strike-slip faults. After verification using method based on the energy content of significant velocities pulses, 16 near-field recordings were recognized as the pulse-like ones, and the pulse period (Tp) was then determined individually. It was found that the extracted values of Tp were generally longer than the prediction value given by the empirical regression model based on the NGA-West2 dataset. The single and multiple degrees of freedom (SDOF and MDOF, respectively) systems were implemented in the computation of inelastic demand and story ductility demand. The results indicated the followings: (1) For the identified pulse-like records, the inelastic demand of SDOF with oscillator period T less than 0.6Tp is much more significant than that for non-pulse-like records when the SDOF nonlinearity level increases. The mean inelastic displacement ratio curve is approximately one standard deviation higher than the mean prediction value in the 0.1 < T/TP < 0.5 range. (2) The maximum ductility demand exists at the bottom story of the 7-story,9-story and 11-story MDOF structure subject to the pulse-like records. For the case of reduced shear strength and stiffness at the bottom story due to removed infill walls, the bottom ductility demand reach more than 10.0 under pulse-like records. These findings support the supposition that large ductility demand and the bottom soft-story mechanism under near-field velocity pulse-like ground motions were the main reasons for severe structural damage of the four near-field mid-rise RC buildings during the Hualien earthquake. •16 near-field stations in Hualien City were classified as having pulse-like records.•The identification results were in agreement with the contour map of pulse-like occurrence probability.•Large ductility demand and the bottom soft-story mechanism were the main reasons for severe structural damage.